2022
DOI: 10.3390/d14121062
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Phytochemical Variability of Endemic Juniperus sabina var. balkanensis from Its Natural Range

Abstract: Juniperus sabina L. var. balkanensis R.P. Adams & Tashev is a recently described endemic variety from the Balkan Peninsula. Its strong sprouting ability and fast vegetative propagation, on one hand, and fragmented distribution, on the other, can lead to lower genetic diversity in local populations and to the differentiation of populations. As there has been no detailed investigation of this variety, we studied Balkan natural populations using phytochemical and molecular markers. Leaf essential oils (EOs) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…balkanensis R.P.Adams & Tashev. [19][20][21][22][23] J. excelsa M. Bieb. (Grecian juniper, JEX) is a monoecious or dioecious tree with scaly adult leaves (decurrent juvenile) with a prominent glandular opening on the adaxial side and purplish-brown seed cones.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…balkanensis R.P.Adams & Tashev. [19][20][21][22][23] J. excelsa M. Bieb. (Grecian juniper, JEX) is a monoecious or dioecious tree with scaly adult leaves (decurrent juvenile) with a prominent glandular opening on the adaxial side and purplish-brown seed cones.…”
Section: Introductionmentioning
confidence: 99%
“…Adams has recently described a tetraploid variety of J. sabina present only in the Balkans and adjacent regions – J. sabina L. var. balkanensis R.P.Adams & Tashev [19–23] . J. excelsa M. Bieb.…”
Section: Introductionmentioning
confidence: 99%
“…sabina extends from Spain in the west to Georgia in the east, whereas var. balkanensis is found in the Iberian, Apennine and Balkan Peninsulas and western Turkey [11][12][13][14][15]. The varieties sabina and balkanensis co-occur only in one locality in Spain, but hybrids were not found there [9].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the midday leaf temperature of potatoes (Solanum tuberosum L.) growing under drought stress was significantly lowered due to increased leaf water potential from the K supply [21]. The balkanensis variety of J. sabina exhibits a substantial drought tolerance [15]; however, factors enhancing its ability to cope with the water deficit have not yet been recognised. The range of var.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation